Trans‐equatorial range of a land bird lineage (Aves: Rallidae) from tropical forests to subantarctic grasslands. (30th October 2015) - Garcia‐R, Juan C.; Elliott, Graeme; Walker, Kath; Castro, Isabel; Trewick, Steven A.
Abstract : Despite the capacity for dispersal, range size varies considerably among birds species. Many species have restricted geographic spread, whilst others routinely travel long distances to reach preferred habitat. These alternatives are well expressed amongst the rails (Rallidae) and a varying tendency for movement results in overlapping distribution patterns. Here, we examine the situation of a particular lineage, the Lewinia rails ( L. mirifica, L. pectoralis and L. muelleri ) that inhabit a very wide spatial and ecological range. Lewinia occurs from the Philippines, north of the equator in Oceania, to Australia and the subantarctic Auckland Islands far to the south. Allopatric distribution and differences in plumage colour result in their treatment as distinct species but our mitochondrial molecular analysis (cyt b and CR) reveals genetic distances of less than < 1%. The genetic and phylogeographical structure in the Lewinia lineage includes shared nuclear sequence alleles and this is consistent with a callibrated multigene phylogeny suggesting trans‐hemispheric dispersal since the middle Pleistocene. Despite this recent history, available morphometric data indicates that the subantarctic population has relatively small wings for its mass, and this implies adaptation away from flight. Lewinia provides a nice example of the way dispersal and adaptation intersect over short time frames to generate diversity.